Konsep Pengangkutan Sampah di Kecamatan Somba Opu, Kabupaten Gowa - Andi Nur’Izzania Aulania; Muhammad Yamin Jinca; Yashinta Kumala Dewi Sutopo (Department of Urban and Regional Planning, Faculty of Engineering, University of Hasanuddin, 2020)
High levels of waste productivity, illegal waste disposal, poor quality of waste facilities, and waste transportation system that has not been running optimally are problems that occur in Somba Opu District, Gowa Regency. The study aimed to identify and actualize an ideal concept of waste transportation in terms of route, mode, and schedule. The research was started from November 2019 to May 2020. This research is located in Somba Opu District, Gowa Regency. Data collection methods are done primarily through observation, interviews, field survey, and documentation. Secondary data was obtained from literatures study and agencies visit. Analysis was done by using synthesis of literatures study, projected population and waste generation, the needs of waste transfer station analysis, waste transportation analysis, and spatial analysis. This study found the concept of waste transportation that will be applied, such as: the alternative route for transporting wastes to Pabentengang Landfill utilizing Jalan Poros Pangkabinanga thus saving ±1 km of distance and 2-3 minutes of travel time, schedule of transporting waste will be done every day above 22.00 to 07.00. in order to minimize the obstacles, and 2 units of waste truck are needed in 2028, 2033, dan 2038 with 3 times transportation ration and improving the quality of waste transportation mode.